Proceedings of the International Conference on Interdisciplinary Language, Literature and Education (ICILLE 2018) 2019
DOI: 10.2991/icille-18.2019.49
|View full text |Cite
|
Sign up to set email alerts
|

Illocutionary Acts of Directive on Lazada_Id Advertising in the Instagram

Abstract: This study aims to analyze the Lazada_Id advertising text from pragmatic point of view through classifying and describing which is focused in the illocutionary speech acts with directive categories. Where the directive category has several types such as: command, orders, requests, and suggestions. This study also aims to provide one thing that is different from research on speech acts. However, this research is not the only research on speech acts that studies data in the form of writing. This study focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Although this interaction via the internet uses 'written utterances', misunderstandings still cannot be avoided. In our assumption, maybe because the people involved in such interaction have different cultural and linguistic backgrounds [11]; [12], [13] therefore the researchers are interested in making an analysis of this subject. Some people, especially on what kind of negotiation patterns underlying such interaction and how the interlocutors manage and/or choose appropriate utterances to keep the interaction going on, are needed [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although this interaction via the internet uses 'written utterances', misunderstandings still cannot be avoided. In our assumption, maybe because the people involved in such interaction have different cultural and linguistic backgrounds [11]; [12], [13] therefore the researchers are interested in making an analysis of this subject. Some people, especially on what kind of negotiation patterns underlying such interaction and how the interlocutors manage and/or choose appropriate utterances to keep the interaction going on, are needed [14].…”
Section: Introductionmentioning
confidence: 99%
“…The directives illocution acts are both commanding and obstructive [14]. Albab, and Setiawan [15] research on Lazada Id's Instagram revealed that directive illocutionary speech actions of the command, request, order, and suggestion types are suitable for convincing customers to read and watch Lazada's status or images, videos due to its peculiar effect. According to the research, the wording on the Lazada Id advertisement uses various illocutionary directive texts to bring clarity to consumers and society.…”
Section: Introductionmentioning
confidence: 99%